(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
The rapid development of digital technology has encouraged the use of language-learning applications to enhance the quality of instruction in elementary schools, including Duolingo as an interactive medium that integrates gamification into the learning process. Previous studies indicate that educational technology holds strong potential to improve students’ motivation, learning independence, and English language skills. This study evaluates the effectiveness of the Duolingo application in improving the English language skills of elementary school students using the Systematic Literature Review (SLR) method on seven articles published between 2020 and 2024. The results of the analysis show that Duolingo contributes positively to improving students’ writing, reading, listening, and speaking skills. The gamification approach applied in this application has been proven to be able to increase learning motivation and student involvement in the learning process. In addition, the time flexibility and accessibility offered allow students to learn independently according to their own pace. However, this study also identifies several obstacles that can hinder the effectiveness of using Duolingo, such as difficulty adapting to technology, limited internet access, and the availability of devices. Some students also experience fluctuations in motivation when there is no variation in learning methods, and the limited feedback from the application makes teacher assistance still necessary to maximize learning outcomes. Therefore, while Duolingo has great potential in supporting English learning in elementary schools, its success still depends on the support of educators as well as adequate technology accessibility. By overcoming these challenges, Duolingo can be an effective learning tool in improving the quality of English education in the digital era. The integration of this application into the curriculum, as well as training for teachers and students, is an important step in maximizing its benefits for learning.